Dysregulated mitophagy and mitochondrial organization in optic atrophy due to OPA1 mutations. (10th January 2017) - Liao, Chunyan; Ashley, Neil; Diot, Alan; Morten, Karl; Phadwal, Kanchan; Williams, Andrew; Fearnley, Ian; Rosser, Lyndon; Lowndes, Jo; Fratter, Carl; Ferguson, David J.P.; Vay, Laura; et al.
Abstract : Objective: To investigate mitophagy in 5 patients with severe dominantly inherited optic atrophy (DOA), caused by depletion of OPA1 (a protein that is essential for mitochondrial fusion), compared with healthy controls. Methods: Patients with severe DOA (DOA plus) had peripheral neuropathy, cognitive regression, and epilepsy in addition to loss of vision. We quantified mitophagy in dermal fibroblasts, using 2 high throughput imaging systems, by visualizing colocalization of mitochondrial fragments with engulfing autophagosomes. Results: Fibroblasts from 3 biallelic OPA1 (−/−) patients with severe DOA had increased mitochondrial fragmentation and mitochondrial DNA (mtDNA)–depleted cells due to decreased levels of OPA1 protein. Similarly, in siRNA-treated control fibroblasts, profound OPA1 knockdown caused mitochondrial fragmentation, loss of mtDNA, impaired mitochondrial function, and mitochondrial mislocalization. Compared to controls, basal mitophagy (abundance of autophagosomes colocalizing with mitochondria) was increased in (1) biallelic patients, (2) monoallelic patients with DOA plus, and (3) OPA1 siRNA–treated control cultures. Mitophagic flux was also increased. Genetic knockdown of the mitophagy protein ATG7 confirmed this by eliminating differences between patient and control fibroblasts. Conclusions: We demonstrated increased mitophagy and excessive mitochondrial fragmentation in primary human cultures associated with DOA plus due to biallelic OPA1 mutations. We previously found that increased mitophagy (mitochondrial recycling) was associated with visual loss in another mitochondrial optic neuropathy, Leber hereditary optic neuropathy (LHON). Combined with our LHON findings, this implicates excessive mitochondrial fragmentation, dysregulated mitophagy, and impaired response to energetic stress in the pathogenesis of mitochondrial optic neuropathies, potentially linked with mitochondrial mislocalization and mtDNA depletion.